Ethical Climate and Moral Intensity in Organizational Management: A Systematic Literature Review on Accountants’ Behavioral Responses - Nur Ainiyah; Hari Setiono; Muhammad Bahril Ilmiddaviq (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
Ethical issues in accounting practice continue to raise concerns about professional judgment and integrity, underscoring the importance of understanding the behavioral determinants of ethical decision-making. This study aims to synthesize prior empirical Research examining the role of ethical climate and moral intensity in shaping accountants' behavioral responses. Using a systematic literature review approach guided by the PRISMA 2020 framework, this study analyzes 20 peer-reviewed empirical articles published between 2020 and 2025. The review is complemented by bibliometric mapping using VOSviewer to identify dominant themes and Research gaps. The findings indicate that ethical climate is a key organizational-level determinant of ethical judgment, ethical intention, and whistleblowing behavior, particularly in caring, rules, and law-and-code climates. Moral intensity emerges as a critical issue-specific factor that shapes ethical awareness and moderates the effect of ethical climate, especially through the magnitude of consequences and social consensus. However, the literature remains dominated by cross-sectional designs and intention-based outcomes, with limited attention to actual ethical behavior. This study contributes an integrative perspective that links organizational ethical context with moral cognition and underscores the need for future Research employing behavioral measures, multilevel designs, and cross-cultural approaches to strengthen the understanding of ethical decision-making in accounting practice in Organizational Management.